Habitat filtering determines the functional niche occupancy of plant communities worldwide. (30th May 2017) - Li, Yuanzhi; Shipley, Bill; Price, Jodi N.; Dantas, Vinícius de L.; Tamme, Riin; Westoby, Mark; Siefert, Andrew; Schamp, Brandon S.; Spasojevic, Marko J.; Jung, Vincent; Laughlin, Daniel C.; Richardson, Sarah J.; et al.
Abstract: How the patterns of niche occupancy vary from species‐poor to species‐rich communities is a fundamental question in ecology that has a central bearing on the processes that drive patterns of biodiversity. As species richness increases, habitat filtering should constrain the expansion of total niche volume, while limiting similarity should restrict the degree of niche overlap between species. Here, by explicitly incorporating intraspecific trait variability, we investigate the relationship between functional niche occupancy and species richness at the global scale. We assembled 21 datasets worldwide, spanning tropical to temperate biomes and consisting of 313 plant communities representing different growth forms. We quantified three key niche occupancy components (the total functional volume, the functional overlap between species and the average functional volume per species) for each community, related each component to species richness, and compared each component to the null expectations. As species richness increased, communities were more functionally diverse (an increase in total functional volume), and species overlapped more within the community (an increase in functional overlap) but did not more finely divide the functional space (no decline in average functional volume). Null model analyses provided evidence for habitat filtering (smaller total functional volume than expectation), but not for limiting similarity (larger functional overlap and larger average functional volume than expectation) as a process driving the pattern of functional niche occupancy. Synthesis . Habitat filtering is a widespread process driving the pattern of functional niche occupancy across plant communities and coexisting species tend to be more functionally similar rather than more functionally specialized. Our results indicate that including intraspecific trait variability will contribute to a better understanding of the processes driving patterns of functional niche occupancy. Abstract : Both the total functional volume and the functional overlap increased with increasing species richness, while the average functional volume did not vary significantly. Habitat filtering is a widespread process driving the pattern of functional niche occupancy across plant communities and coexisting species tend to be more functionally similar rather than more functionally specialized. Editor's Choice